Site-selective ethanol conversion over supported copper catalysts - Sato, Andre G.; Volanti, Diogo P. [UNESP]; de Freitas, Isabel C.; Longo, Elson [UNESP]; Bueno, Jose Maria C. (Elsevier B.V., 2012)
The origin and influence of active sites on supported copper catalysts, and their catalytic properties for ethanol conversion, were investigated using Cu/SiO2, Cu2O/SiO2, and Cu/ZrO2. Diffuse reflectance infrared Fourier transform spectroscopy of adsorbed CO revealed that Cu1+ was more prevalent than Cu-0 species at the Cu/SiO2 surface, and that Cu-0 was the main species on Cu/ZrO2. The Cu1+/Cu-0 pair provided by Cu/SiO2 generates sites that are highly selective for the dehydrogenation of ethanol. Ethyl acetate can be formed from ethanol and acetaldehyde at ZrO2 or Cu surfaces. A combination of the Cu1+/Cu-0 pair and Cu-0 interfaced to ZrO2 is needed to efficiently transform ethanol to ethyl acetate. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: DRIFTS; XANES; Zirconia polymorphs; Hydrogen; Copper catalysts; Ethanol chemistry